Influence of Intellectual Capital and Corporate Governance on Company Financial Performance: Study on Mining Sector Companies Listed on The Indonesia Stock Exchange for 2016-2020 Period - Nelli Novyarni; Nora Hutabarat; Reni Harni (Iapa Proceedings Conference, 2022)
This study aims to determine the effect of intellectual capital and corporate governance on the company's financial performance. Intellectual capital measurement uses three independent variables, namely Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Value Added Structural Capital (STVA), while corporate governance is proxied by institutional ownership, foreign ownership, and the proportion of independent commissioners, to the company's financial performance is proxied by the Return of Assets (ROA). The study was conducted on mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. By using purposive sampling method, obtained a sample of 10 companies. The results showed that Value Added Capital Employed (VACA), Structural Capital Value Added (STVA), and institutional ownership had an effect on the company's financial performance, while Value Added Human Capital (VAHU), and the proportion of independent commissioners had no significant effect on financial performance.